Okun’s Law in the Eurozone in the Post-Crisis era - Bodeneyev, Azamat; Slaný, Martin, 1982-; Bertoli, Paola; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2019)
Eurozone has experienced two tragic financial crises during 2008-2013. When the global financial crisis hit, it exposed all the inherent flaws of the eurozone. During the crisis virtually all countries of the euro area has been facing high unemployment rate and from the general perspective of regulators, low economic growth is a trigger mechanism for high unemployment. This paper seeks to investigate whether the relationship between real gross domestic product and unemployment is significant for the eurozone countries for the period 2002-2018. Panel quarterly data analysis is employed to ascertain the association among growth and unemployment in the three periods (2002:1-2008:3; 2008:4-2018:4; 2002:1-2018:4) for the nineteen countries of the euro area. The Hodrick-Prescott filter is applied to several macroeconomic time series in order to illustrate the picture of the effect of Global Recession and Eurozone crisis. The meticulous analysis and description of the datasets are provided as well. Different methods are employed to better understand the theory and compare the results to the original findings. The key finding of this paper is that economic growth has more significant impact on the male unemployment than on the female unemployment in the eurozone. Moreover, Okun’s coefficient for the post-crisis era is found to be much more significant than for the pre-crisis era.
Vedoucí práce: Martin Slaný
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses